MAPPING THE SHARIAH SUPERVISORY BOARD ROLE IN ISLAMIC FINANCIAL INSTITUTION: AN ANALYTIC NETWORK PROCESS (ANP) APPROACH - Shellvy Lukito; Sepky Mardian; Lutfi Zulkarnain (Imara: JURNAL RISET EKONOMI ISLAM, 2021)
This study aims to reveal the priority problems related to the Shariah Supervisory Board (SSB) and their solutions in monitoring the principles of sharia. This study uses a non-parametric approach with the Analytic Network Process (ANP) method. Primary data is obtained through in-depth interviews with academics and practitioners who have directly become the Sharia Supervisory Board. This study found that the main problem with the role of the Sharia Supervisory Board is independence, where there are multiple SSB positions in several Islamic financial institutions. Currently, the priority solutions agreed upon by the informants can be minimized by holding multiple positions in different sectors. This solution is expressed by considering conditions that are not yet ideal, where the number of DPS is still limited compared to the need for sharia supervision in Islamic financial institutions.